Tobacco Use Among the Youth in India: Evidence From Global Adult Tobacco Survey-2 (2016-2017) - Shekhar Grover; Tanu Anand; Jugal Kishore; Jaya Prasad Tripathy; Dhirendra N Sinha (SAGE Publishing, 2020)
Background: Worldwide, tobacco use is a serious public health concern affecting the youth. A vast majority of tobacco users start using tobacco well before the age of 18 years which has enormous psychosocial and health effects. Objectives: To estimate the prevalence of individual forms of tobacco usage among youth aged 15 to 24 years and to assess the association of sociodemographic factors with tobacco use. Methods: The source of data was a cross-sectional GATS-2 survey in India (analysed using SPSSv17.0) which used a multistage, geographically stratified cluster sampling method. Bivariate analysis was done for evaluation of the possible association of tobacco use with sociodemographic factors. Multivariable logistic regression analysis was conducted to determine the relative strength of association between those factors and tobacco use. Results: There were 13 329 respondents (44.9% males and 55.1% females) aged 15 to 24 years. Overall, 11.9% of respondents were using tobacco. The prevalence of smoke and smokeless tobacco usage was 5% and 10.9%, respectively, whereas 2% of respondents reported dual usage. The odds of using any form of tobacco were significantly higher among respondents aged 20 to 24 years (odds ratio [OR]: 2 [1.76-2.77]) who were primarily residing in rural areas (adjusted odds ratio [aOR]: 1.36 [1.2-1.54]) and were unmarried (aOR: 1.56 [1.37-1.88]). The odds of using any form of tobacco were significantly lower among females (aOR: 0.21 [0.19-0.24]), literate individuals (aOR: 0.33 [0.29-0.37]), and those who were unemployed/students/homemakers (aOR: 0.44 [0.39-0.50]). Conclusions: The overall tobacco usage of 11.9% among young people in the age group of 15 to 24 years is a matter of concern. The study identified several sociodemographic factors significantly associated with tobacco use, implying the need for designing interventions considering social vulnerabilities of youth.